Effect of high‐pressure processing on the polysaccharides content and antioxidant activity of fresh Dendrobium officinale juice. Issue 5 (15th August 2018) - Liang, Juan; Guo, Sai; Zhou, An; Hui, Ai Ling; Zong, Kai; Yu, Nian Jun; Peng, Dai Yin
Abstract: Fresh Dendrobium officinale possessed higher activities compared with the dried ones. High‐pressure processing (HPP) could effectively enhance the content and activities of Dendrobium officinale polysaccharides (DOPS) which is the main active ingredients of fresh Dendrobium officinale juice (FDOJ). Pressure, temperature, and holding time were optimized using response surface methodology to enhance DOPS content. The DOPS molecular weights (Mw) compositions and antioxidantive activities of FDOJ under the optimal HPP conditions (HDOJ) and FDOJ samples were also determined. The result indicated that under the optimal conditions, the highest (DOPS) content obtained was 315.4 mg/100 mL, which represented 37.7% more than that in FDOJ. The high‐performance gel permeation chromatography (HPGPC) result found that Mw compositions of the FDOJ and HDOJ samples were different. Both the in vitro and in vivo results revealed that the antioxidant activities of the HDOJ samples were significantly superior to that of the FDOJ samples. Practical applications: As we know, HPP has been an attractive way to replace conventional heat treatments for the preservation of foods. This research investigated the utility of HPP for FDOJ. Results showed that, much more than prolonged shelf life of FDOJ, HPP could also enhance the content of DOPS which was the most important active ingredient and therefore improve the antioxidant activities of FDOJ. The results of this study could both expand the application of HPP in the development of the fresh Dendrobium officinale and related products and help to facilitate further development of fresh Dendrobium officinale industries.